Chemical composition of essential oils from Citrus species peels and its insecticidal potential effect on cowpea. - *, Raymond; Yilwa, R. A.,; Aina, V. M.,; S. G., V. O., Joseph (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Volatile oils from the peels of sweet orange (Citrus sinensis) lemon (Citrus limon) and grape fruit (Ctrus paradiisi) were comparatively evaluated on cowpea plant at flowering and at pod stage weekly four weeks.the volatile oil were extracted by GC/MS,the main compound of the peels essential oil were oleic acid, benzene 1-ethyl -2methyl,decane and undecane which constitute the bulk of the three oil in these percentages (22.56%, 23.19%, and 24.26%, 3.6%, 10.32% and 7.90%, 15.24%, 16.28% and 13.64%, 9.42%, 15.74% and 12.34%) for sweet Orange, Grape, and Lemon fruits. These oils were used for the growing of cowpea plant, the citrus peels had insecticidal properties